2004
DOI: 10.4049/jimmunol.173.12.7109
|View full text |Cite
|
Sign up to set email alerts
|

Notch Governing Mature T Cell Differentiation

Abstract: The differentiation of naive T cells to effector/memory T cells is regulated by a variety of factors. The recent advance of the contribution of Notch signaling in this differentiation step has provided a new path to better understand the acquisition or persistence of effector function of mature T cells. In this review, we summarize emerging and, in some points, conflicting evidence for Notch signaling on mature T cell activation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Several recent reports suggest a role for the Notch pathway during differentiation of mature naïve T cells into functionally distinct effector T cell subsets in the periphery. Due to the complexity of potential Notch receptor/ligand interactions the molecular details of these processes are not yet clearly defined; a fact that is illustrated by a number of inconsistent reports published on the function of Notch in peripheral T cell activation and differentiation (reviewed in [11,40]). …”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports suggest a role for the Notch pathway during differentiation of mature naïve T cells into functionally distinct effector T cell subsets in the periphery. Due to the complexity of potential Notch receptor/ligand interactions the molecular details of these processes are not yet clearly defined; a fact that is illustrated by a number of inconsistent reports published on the function of Notch in peripheral T cell activation and differentiation (reviewed in [11,40]). …”
Section: Discussionmentioning
confidence: 99%
“…There is a debate as to whether Notch signaling enhances T cell activation or suppresses T cell function in murine and human systems (38). Notch ligands have been shown to differentially affect T cell differentiation (16,(23)(24)(25), but the molecular events underlying the role of Notch in directing naive T cell differentiation toward the Th1, Th2, or Treg lineages are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling controls mature T cell differentiation and activation by directly regulating transcription of effector molecules (7,8,14,15). In particular, our group has recently demonstrated that Notch2 signaling directly controls CTL effector molecules, including granzyme B, by integrating RBP-J and CREB1 (8).…”
Section: Discussionmentioning
confidence: 99%